(3GdebOeI aj JLhjO GdbQBfs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s
(3ChdgG (B:s
(3hHYO Ef gPg ebOeI ajeG Ydi bGQFg Gf jYdeg EPG hLHJ Ydjge eMJe bHd GdTQhY ChdkG Bf jYdehG s
(3BNQgG (B:s
(3hbO JbVi fXei GdebOeI efi dbGQF GdbQBf JbOeg hGdMeO ddg dgG NJGe Je GdUdGI HYOO hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdSGOSs
(3YdjgG Jedcs
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B((3YGe (B9214) s
Keywords: (3GdbQGAGJ hGdJLhjOs